(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The rate of ICT growth in the Nigerian Navy Forces is still appallingly low. Given the aforementioned factor, assessing the Nigerian Navy Force’s ICT maturity level is critical as this could offer helpful insight into how to successfully integrate ICT into the Nigerian Navy Force. This research work adopted the Small-size and Medium-size Enterprises ICT Maturity model in examining and measuring the optimal utilization of technology in Nigeria Navy Force. A questionnaire designed after ICT Maturity Model of SMEs containing forty-five research questions guided this project work. The questionnaires were afterward sorted and coded according to the responses from the 30 Senior Commissioned Officers, 30 Junior Commissioned Officer and 30 Non-Commissioned Officers that participated in this research survey using the indicator stage value in the coding process. The required ICT Maturity Indexes were extracted from the respective commands and were subsequently calculated using the Microsoft Excel Spreadsheet. Nigerian Navy Commands and unit were carefully selected and their ICT calculated to be significantly substantial with ICT maturity level at 0.58. This result analysis shows that ICT’s innovations and capacities are yet to be effectually and efficiently exploited within the Nigerian Navy Force. The research offers helpful insight into how to successfully integrate and measure the utilization of ICT potentials in the Nigerian Navy Force for its training and operations. The knowledge acquired would also be very beneficial for planning, budgeting, and setting funding priorities that will be specifically focused on the requirements area.